Immobilization of pectinase on polyethyleneimine based support via spontaneous amino-yne click reaction - OKTAY, BURCU; KAYAMAN APOHAN, NİLHAN; DEMİR, SERAP (ELSEVIER, 2020)
The immobilization of an enzyme can improve catalytic activity, stability, and reusability of its. In this study, we investigated a new method for enzyme immobilization. Alkyne-pectinase was first immobilized on the polyethyleneimine-based cryogel via a spontaneous amino-yne click reaction under very mild conditions and then the apple juice was clarified. Amino-yne click reactions do not need any photoinitiator or catalyst, unlike other click reactions. The immobilization efficiency of the alkyne pectinase was 90%. The immobilized enzyme continued to retain 70% of its initial activity after 60 days. An improvement observed in the pH tolerance in the range of 6.5-8.0. The higher thermal tolerance of the immobilized pectinase was increased above 50 degrees C. Immobilized pectinase showed 100% activity at 55 degrees C and pH 6.5. The clarification rate of apple juice was achieved about 50% by the pectinase immobilized support. (C) 2020 Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Click reaction; Enzyme immobilization; Pectinase; MAGNETITE NANOPARTICLES; ASPERGILLUS-NIGER; ALPHA-AMYLASE; FACILE TOOL; ALGINATE; ENZYME; APPLE; POLYMERIZATION; TRYPSIN; CLARIFICATION